Competence, Understanding and Role of Apparatus on Management Accountability Moderated Internal Control Systems - Heidy Devi; Syntia Riswati; Agus Sudrajat (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
This study aims to determine the Effect of Competence, Understanding, and Village Apparatus on Management Accountability with the Internal Control System as a Moderating Variable (Case Study in Magetan Regency). Sampling with primary data was obtained directly from 67 villages with 201 respondents in Magetan Regency. This type of research uses quantitative research. The sampling technique used was the purposive sampling method. Data collection was carried out by distributing questionnaires to village officials who served as the Village Head, Village Treasurer, and Village Secretary. The assessment of variables in the research instrument uses a Likert scale. The analysis technique used is multiple linear regression analysis. The results of the analysis show that the Village Apparatus Competence significantly Affects Village Fund Management Accountability, Village Apparatus Understanding Affects Village Fund Management Accountability, Village Apparatus Role Affects Village Fund Management Accountability, and the Internal Control System can Moderate Village Apparatus Competence Against Village Fund Management Accountability, Internal Control System Unable to Moderate Understanding of Village Apparatus towards Accountability of Village Fund Management and Internal Control System able to Moderate Village Role to Accountability of Village Fund Management.